Saharan dust levels in Greece and received inhalation doses - C. Mitsakou; G. Kallos; N. Papantoniou; C. Spyrou; S. Solomos; M. Astitha; C. Housiadas (Atmospheric Chemistry and Physics, 2008)
The desert of Sahara is one of the major sources of mineral dust on Earth, producing around 2×108 tons/yr. Under certain weather conditions, dust particles from Saharan desert get transported over the Mediterranean Sea and most of Europe. The limiting values set by the directive EC/30/1999 of European Union can easily be exceeded by the transport of desert dust particles in the south European Region and especially in urban areas, where there is also significant contribution from anthropogenic sources. In this study, the effects of dust transport on air quality in several Greek urban areas are quantified. PM10 concentration values from stationary monitoring stations are compared to dust concentrations for the 4-year period 2003–2006. The dust concentration values in the Greek areas were estimated by the SKIRON modelling system coupled with embedded algorithms describing the dust cycle. The mean annual dust contribution to daily-averaged PM10 concentration values was found to be around or even greater than 10% in the urban areas throughout the years examined. Natural dust transport may contribute by more than 20% to the annual number of exceedances – PM10 values greater than EU limits – depending on the specific monitoring location. In a second stage of the study, the inhaled lung dose received by the residents in various Greek locations is calculated. The particle deposition efficiency of mineral dust at the different parts of the human respiratory tract is determined by applying a lung dosimetry numerical model, which incorporates inhalation dynamics and aerosol physical processes. The inhalation dose from mineral dust particles was greater in the upper respiratory system (extrathoracic region) and less significant in the lungs, especially in the sensitive alveolar region. However, in cases of dust episodes, the amounts of mineral dust deposited along the human lung are comparable to those received during exposure in heavily polluted urban or smoking areas.